Scaffold-based Strategies for Direct Pulp Capping in Animal Models: A Systematic Review and Meta-analysis - de Queiroz, Gisele Brito; Julião Costa , Gabriella Alves; de Paulo, João Paulo Mota; Vitor Nobre, Átila Vinicius; Cetira Filho, Edson Luiz; de Barros Silva, Paulo Goberlânio; Giroux Rodrigues, Nara Sousa; de Paulo Aragão Saboia, Vicente; Araújo Cunha, Diana (Iranian Endodontic Journal, 2025)
Introduction: The dental pulp is a specialized connective tissue responsible for maintaining tooth vitality through a complex interplay of cellular, vascular, and immunological components. Despite the clinical use of conventional capping materials, their limited regenerative potential often results in pulp devitalization and compromised structural integrity. Recent advances in tissue engineering, particularly the application of three-dimensional scaffolds, have demonstrated promising outcomes in promoting dentin-pulp complex regeneration and biomimetic tissue repair. This systematic review and meta-analysis evaluated the efficacy of three-dimensional matrices, with or without bioactive materials, as direct pulp capping agents in animal models. Outcomes included cellularity, dentin thickness, dentin bridge formation, dystrophic calcification, inflammation control, and pulp organization compared to commercial materials. Materials and Methods: A comprehensive search was conducted in indexed databases and gray literature. A random-effects meta-analysis used standardized mean differences and the inverse variance method. Heterogeneity (I²), publication bias (Egger’s and Begg’s tests), and risk of bias (SYRCLE’s RoB tool) were assessed. Statistical analyses were conducted using RevMan (P<0.05). Results: Seventeen studies met the inclusion criteria, with 13 included in the meta-analysis. The risk of bias was predominantly low, yet the certainty of evidence was very low. Scaffolds significantly enhanced cellularity (P=0.02; I²=91%), dentin thickness (P<0.00001; I²=87%), and inflammation control (P=0.03; I²=20%) compared to controls. No significant differences were observed for dentin bridge formation (P=0.30; I²=63%), dystrophic calcification (P=0.14; I²=32%), or pulp organization (P=0.10; I²=0%). Conclusion: Three-dimensional scaffolds demonstrated potential in promoting cellular activity, dentin formation, and inflammation control. However, their impact on dentin bridge formation, pulp organization, and dystrophic calcification remains inconclusive. Further high-quality studies are required to validate their clinical applicability.